A facile approach to therapeutic angiogenesis using a platelet concentrate and microsphere composite. Issue 6 (7th November 2021) - Hendow, Eseelle K.; Day, Richard M.
Abstract: Stimulating revascularization of under perfused tissue is a key challenge in regenerative medicine. A variety of approaches using soluble biotherapeutic agents have been investigated in recent years but each have yielded limited potency or raised concerns regarding safety. This study reports on the finding that the pro‐angiogenic secretome released from platelet concentrates is significantly enhanced when combined with highly porous biodegradable polymer microspheres. These findings suggest a topically applied autologous platelet concentrate‐biomaterials based approach may serve as a facile and broadly applicable platform to achieve therapeutic angiogenesis in ischemic tissue or where preservation of tissue perfusion and viability is required. Abstract : Highly porous biodegradable TIPS microspheres provide a novel platform to enhance the secretion of pro‐angiogenic factors from platelet concentrates. This easy‐to‐use approach enables production of a highly pro‐angiogenic composite within minutes and offers a new strategy for enhancing angiogenesis that could benefit a range of cardiovascular and peripheral vascular diseases by replicating the natural profile of angiogenic factors associated with physiological angiogenesis.